Links Among Crop Diversification, Microbial Diversity, and Soil Organic Carbon: Mini Review and Case Studies - Wooliver, Rachel; Kivlin, Stephanie N.; Jagadamma, Sindhu (Frontiers in Microbiology, 2022)
Interactions between species above- and belowground are among the top factors that govern ecosystem functioning including soil organic carbon (SOC) storage. In agroecosystems, understanding how crop diversification affects soil biodiversity and SOC storage at the local scale remains a key challenge for addressing soil degradation and biodiversity loss that plague these systems. Yet, outcomes of crop diversification for soil microbial diversity and SOC storage, which are key indicators of soil health, are not always positive but rather they are highly idiosyncratic to agroecosystems. Using five case studies, we highlight the importance of selecting ideal crop functional types (as opposed to focusing on plant diversity) when considering diversification options for maximizing SOC accumulation. Some crop functional types and crop diversification approaches are better suited for enhancing SOC at particular sites, though SOC responses to crop diversification can vary annually and with duration of crop cover. We also highlight how SOC responses to crop diversification are more easily interpretable through changes in microbial community composition (as opposed to microbial diversity). We then develop suggestions for future crop diversification experiment standardization including 1) optimizing sampling effort and sequencing depth for soil microbial communities and 2) understanding the mechanisms guiding responses of SOC functional pools with varying stability to crop diversification. We expect that these suggestions will move knowledge forward about biodiversity and ecosystem functioning in agroecosystems, and ultimately be of use to producers for optimizing soil health in their croplands.